Inefficacy of albendazole sulphoxide and ivermectin for the treatment of bovine parasitic otitis caused by rhabditiform nematodes Ineficácia do sulfóxido de albendazole e da ivermectina no tratamento da otite parasitária bovina causada por nematóides rhabditiformes - Guilherme G. Verocai; Julio I. Fernandes; Thaís R. Correia; Raquel M.P.S. Melo; Pedro Afonso M. Alves; Fabio B. Scott; Laerte Grisi (Pesquisa Veterinária Brasileira, 2009)
The purpose of this study was to evaluate the efficacy of orally administered albendazole sulphoxide and pour-on ivermectin for the treatment of bovine parasitic otitis caused by rhabditiform nematodes. Eighteen Gyr cows presenting clinical otitis were divided in three groups with six animals each. The first one did not receive any treatment (control group). The second one was treated with 0.5% pour-on ivermectin, 500µg/kg of body weight, and the third group was treated with oral 6% albendazole sulphoxide, at 6.0mg/kg. Both ear canals of each animal were reexamined on days 7 and 21 post treatment. The animals in the control group remained infected throughout the days of observation. Ivermectin treatment did not show effectiveness on days 7 or 21 post treatment. The albendazole sulphoxide treatment had an efficacy of 16.7 and 25% on days 7 and 21, respectively. Further studies are required to assess an effective treatment for this parasitic disease, especially via alternative administration routes, because of its significant impact on Bos taurus indicus cattle breeding in Tropical and Subtropical Regions. O objetivo deste estudo foi avaliar a eficácia do sulfóxido de albendazol administrado oralmente e da ivermectina "pour-on" no tratamento da otite parasitária bovina causada por nematóides rhabditiformes. Dezoito vacas Gir apresentando otite clínica foram divididas em três grupos de seis animais cada. O primeiro não recebeu tratamento (grupo controle). O segundo foi tratado com ivermectina "pour-on" a 0,05% na dose de 500µg/kg de peso vivo. O terceiro grupo foi tratado com sulfóxido de albendazol oral a 6% na dose 6,0mg/kg. Os condutos auditivos de todos os animais foram reexaminados nos dias 7 e 21 pós-tratamento. Os animais do grupo controle permaneceram infectados nos dias de observação. O tratamento com ivermectina não demonstrou eficácia alguma para os dias 7 e 21 pós-tratamento. O tratamento com sulfóxido de albendazol obteve 16,7 e 25% de eficácia nos dias 7 e 21, respectivamente. Mais estudos são necessários para determinação de tratamentos eficazes para tal doença parasitária, especialmente através de vias alternativas de administração, por causa de seu significante impacto na criação de Bos taurus indicus nas Regiões Tropical e Subtropical.